Teledermatology: An updated overview of clinical applications and reimbursement policies - M. Campagna; F. Naka; J. Lu (Wolters Kluwer, 2017)
Telemedicine is an emerging field in healthcare that provides services from different medical specialties to patients all around the world. One of the specialties in telemedicine, teledermatology, has grown exponentially as a cost-effective way to implement dermatological healthcare to underserved areas and populations. This article reviews the literature that pertains to the cost-effectiveness, reliability, public access, patient satisfaction, and reimbursement policies of teledermatology. Teledermatology was found to be cost-effective and reliable in reducing in-person visits and time away from work, and allows for the faster delivery of care. However, reimbursement policies for teledermatology services are rather new and vary significantly from state to state. As public interest in and access to teledermatology continue to grow, the future of teledermatology depends on the development of new technology as well as quality improvement strategies and the evolution of sustainable reimbursement policies. Keywords: teledermatology, store and forward teledermatology, real-time teledermatology, cost-effectiveness, reimbursement policy